2015
DOI: 10.1002/aenm.201500865
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Compatibility of Solvate Ionic Liquids with Sulfide Solid Electrolytes: Toward Favorable Ionic Contacts in Bulk‐Type All‐Solid‐State Lithium‐Ion Batteries

Abstract: The excellent stability of sulfide solid electrolytes with solvate ionic liquids Li(triethylene glycol dimethyl ether)bis(trifluoromethanesulfonyl)imide (Li(G3)TFSI), and their application for high‐performance, all‐solid‐state lithium‐ion batteries are successfully demonstrated. The addition of a small amount of Li(G3)TFSI gives an alternative ionic pathway through normally poor solid–solid contacts, leading to a dramatic increase in LiFePO4 composite electrode capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 42 publications
6
118
1
Order By: Relevance
“…The well matched result identifies that ACN or SN is stable with LGPS and can be used as solvent or plasticizer in PEO/LGPS composite electrolyte. In addition, it is reported that the ether oxygens can do nucleophilic attack Li 10 GeP 2 S 12 solid electrolytes [27]. The XRD pattern of LGPS after storing in PEO for seven days (Fig.…”
Section: Characterization Of Composite Spesmentioning
confidence: 96%
See 2 more Smart Citations
“…The well matched result identifies that ACN or SN is stable with LGPS and can be used as solvent or plasticizer in PEO/LGPS composite electrolyte. In addition, it is reported that the ether oxygens can do nucleophilic attack Li 10 GeP 2 S 12 solid electrolytes [27]. The XRD pattern of LGPS after storing in PEO for seven days (Fig.…”
Section: Characterization Of Composite Spesmentioning
confidence: 96%
“…Finally, the addition of Li salt could significantly suppresses dissolution of LGPS. The strong coordination of oxygen to Li ions will lessen the nucleophilicity of oxygen, resulting in the significantly reduced reactivity as the reference mentioned [27]. Consequently, in PEO/LGPS systems, the PEO is relatively compatible with the sulfide solid electrolyte LGPS as well.…”
Section: Characterization Of Composite Spesmentioning
confidence: 97%
See 1 more Smart Citation
“…One type of SHE is the careful combination of two kinds of existing electrolyte (e.g., LOEs, ionic liquids (ILs), solid polymer electrolytes (SPEs) and solid inorganic electrolytes (SIEs)). Representative combinations include ILs–SIEs, LOEs–SPEs, SIEs–SPEs, etc. ; for example, as shown in Figure a, the sandwich‐like solid hybrid electrolyte comprehensively utilizes the superior wettability and strong adhesion strength of the SPE to increase the contact area toward bulk lithium anode.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…However, the huge interfacial resistance, originating from the inferior solid‐solid contact and significant interfacial reactions at both cathode and anode interfaces, restricts the electrochemical performance of all‐solid‐state lithium batteries . To address the cathode interface issues, various strategies have been proposed over the past years, for example, using soluble SEs to coat on active materials to increase the electrode–electrolyte contact area, adding some ionic liquids to enhance the ionic contact, and using a buffer layer to suppress the interfacial reactions, such as Li 4 Ti 5 O 12 and LiNbO 3 . In a sharp contrast to the great progress on the cathode interface, little progress has been made on the anode interface, especially using lithium (Li) metal as the anode, because the challenges at the interface between Li metal and SEs are very difficult to address, such as the remarkable interfacial reactions, Li dendrite formation, and volume change.…”
Section: Introductionmentioning
confidence: 99%